PEMBERDAYAAN KELOMPOK TANI SAYUR MELALUI PENERAPAN PERTANIAN SEHAT DI SENTRA PETANI SAYUR DESA BOKOR KECAMATAN TUMPANG KABUPATEN MALANG, JAWA TIMUR - Aini, Nurul; Yamika, Wiwin Sumiya Dwi; Yurlisa, Kartika; Cholid, Fery Abdul; Amalia, Faizatul; Prasetyo, Joko (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
The empowerment activity was motivated by excessive use of inorganic fertilizers, chemical pesticides and herbicides in the process of vegetable cultivation and other agricultural commodities in the vegetable center of Bokor Village. The high cost of labor for weed control causes farmers to overuse herbicides. On the long period, chemical residues can endanger consumer?s health. The objectives of this service are: 1) Increasing awareness of farmers to cultivate vegetables that are safe for consumption with the principles of healthy farming; 2) Reducing damage to agricultural ecosystems due to unhealthy agricultural practices. Mentoring activities are carried out during May-September 2018, with a target of 20 participants. The methods of activities that carried out was a survey and discussion of the implementation of healthy farming with the Bokor Village farmer group; comparative study on the Brenjonk Organic Community, Trawas, Mojokerto; then followed by mentoring vegetable cultivation using biological agents in the study plot. From the results of the mentoring activity, it can be concluded: 1. It has provided knowledge and skills to farmers to implement healthy farming, 2. It has been running quite effectively by looking at the results of evaluations that are in line with the achievement targets.abstrakKegiatan pemberdayaan dimotivasi oleh penggunaan berlebihan pupuk anorganik, pestisida kimia dan herbisida dalam proses budidaya sayuran dan komoditas pertanian lainnya di pusat sayur di Desa Bokor. Tingginya biaya tenaga kerja untuk pengendalian gulma menyebabkan petani terlalu sering menggunakan herbisida. Dalam jangka panjang, residu kimia dapat membahayakan kesehatan konsumen. Tujuan dari layanan ini adalah: 1) Meningkatkan kesadaran petani untuk menanam sayuran yang aman dikonsumsi dengan prinsip pertanian sehat; 2) Mengurangi kerusakan ekosistem pertanian karena praktik pertanian yang tidak sehat. Kegiatan pendampingan dilakukan selama Mei-September 2018, dengan target 20 peserta. Metode kegiatan yang dilakukan adalah survei dan diskusi pelaksanaan pertanian sehat dengan kelompok tani Desa Bokor; studi banding pada Komunitas Organik Brenjonk, Trawas, Mojokerto; kemudian dilanjutkan dengan pendampingan budidaya sayuran menggunakan agen biologi di plot studi. Dari hasil kegiatan pendampingan, dapat disimpulkan: 1) Telah memberikan pengetahuan dan keterampilan kepada petani untuk menerapkan pertanian sehat, 2) Telah berjalan cukup efektif dengan melihat hasil evaluasi yang sejalan dengan pencapaian target.